Activists in City Hall : the progressive response to the Reagan era in Boston and Chicago - Clavel, Pierre (Cornell paperbacks., 2010)
"This energetic and accessible account of progressive successes and failures in a range of American cities in the 1970s and 1980s, including the author's in-depth original research on Boston and Chicago, provides an ideal gateway to the future. Brimming with insights and thoughtful commentary on political strategies, it could be used as a springboard by coming generations of activists and planners."--G. William Domhoff, Unversity of California, Santa Cruz, author of Who Rules America?